Measurement of Conjectural Variations in Oligopoly - Iwata, Gyoichi (Econometrica, 1974)
[This paper proposes a method for measuring the numerical value of the conjectural variation which has been a key concept in oligopoly theories. The statistical property of the estimator for the conjectural variation is examined and two statistical tests are presented. One is a test for the hypothesis that the conjectural variation is a specified value. The other is designed for the hypothesis that there is a certain type of collusion among oligopoly firms. These are applied to the Japanese flat glass industry.]